IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT BY WATCHING MOVIE - Yohanna Situmeang and Busmin Gurning (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study was attempted to improve students’ achievement in writing narrativetext by watching movies. This study was conducted by using classroom action researchin two cycles. Cycle I consisted of four meetings while Cycle II consisted of twomeetings. The subject of the research was class VIII-A SMP SWASTA IMMANUELMEDAN. The number of the students was 34. To collect the data, the instruments werequantitative and qualitative data. The quantitative data was the scores of the studentsand the qualitative data was interview sheets, observation sheets, and diary notes. Basedon the writing score, students’ score were improving in every test. It can be seen inOrientation test, Test I in Cycle I, and Test II in Cycle II. In Orientation test, the meanscore was 37.94 then it was improved to 65.85 in Test I. In the end of cycle II, the meanscore for test II was again improved to 83.41. Based on interview sheets, observationsheets and diary notes, it was found that teaching-learning process ran well. In line withthe data, it showed that the application of watching movies significantly improvedstudent’s achievement in writing narrative text. English teachers were suggested to givemovies to be watched as guidance on students’ narrative writing in the class.